INTRODUCTION TO IN VITRO CULTURE OF CRATAEGUS AMBIGUA AND FEATURES OF MEDIUM-TERM DEPOSIT - Rakhimzhanova , A.O.; Kali , B.R.; Manabayeva , S.A. (Eurasian Journal of Applied Biotechnology, 2025)
The hawthorn (Crataegus ambigua) is a valuable species used for landscaping, medicinal purposes, and breeding. However, the decline of its natural populations underscores the need for effective microclonal propagation and preservation methods. This study conducted a comparative analysis of seed sterilization methods and obtained sterile seeds and micromasses. The influence of growth regulators, such as 6-BA, GA₃, IBA, and IAA, on microclonal propagation and rhizogenesis was also examined. Optimizing the conditions for slow growth is important for medium-term storage and the sustainable use of this species. These results can be used to develop effective protocols for the clonal micropropagation of C. ambigua, which is important for its conservation and introduction into breeding and reintroduction programs.